Influence of longan packed bed arrangement on air flow pattern under forced-air convection - Jaturonglumlert S. (2017)
This paper presents the experimental and theoretical investigations of the influence of forced-air convection system for SO 2 fumigation of fresh longan (Dimocarpus longan Lour.) on a pilot scale. Two different packing arrangements of longan (to generate different air flow patterns) were studied under forced-air and circulating-air convections. The computational fluid dynamics (CFD) approach was applied to simulate the air flow through longan packed beds to estimate the physical condition taking place inside the beds. It was found that the CFD simulation predicted the air flow pattern with an average error within 20% of the experimental values. Simulation indicates that forced-air convection yielded better air penetration through the longan packed bed than circulating-air convection. The packed bed arrangement of 2×2×4 (column×row×stack) exhibited better air-flow distribution than that of 1×4×4. The SO 2 residue distribution on the fumigated longan corresponded well with the trend of CFD air flow simulation. Thus forced-air convection for SO 2 fumigation can be used as an effective tool to extend shelflife of fresh longan. This work provides basic understanding of how forced-air convection affects the SO 2 fumigation and can be further extended to a simulation of SO 2 fumigation by forced-air convection on longan on a commercial.